2012
DOI: 10.1128/aac.05403-11
|View full text |Cite
|
Sign up to set email alerts
|

Further Insights into the Mode of Action of the Lipoglycopeptide Telavancin through Global Gene Expression Studies

Abstract: bTelavancin is a novel semisynthetic lipoglycopeptide derivative of vancomycin with a decylaminoethyl side chain that is active against Gram-positive bacteria, including Staphylococcus aureus strains resistant to methicillin or vancomycin. A dual mechanism of action has been proposed for telavancin involving inhibition of peptidoglycan biosynthesis and membrane depolarization. Here we report the results of genome-wide transcriptional profiling of the response of S. aureus to telavancin using microarrays. Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
4
28
0
Order By: Relevance
“…In contrast, the expression of the enterotoxin gene set7 decreased with OHM in LAC but not LAC⌬agr, and OHM had no effect on the expression of the saeR component of the SaeRS virulence regulator. Likewise, the transcription of genes involved in the stress response (asp23, crtM, and clpB) was not altered by OHM, suggesting that OHM does not induce a general stress response in LAC under the conditions tested (50)(51)(52)(53)(54). Among the metabolism genes examined, OHM had no significant effect on the transcription of the genes involved in electron transport (atpG and sdhA).…”
Section: Resultsmentioning
confidence: 87%
“…In contrast, the expression of the enterotoxin gene set7 decreased with OHM in LAC but not LAC⌬agr, and OHM had no effect on the expression of the saeR component of the SaeRS virulence regulator. Likewise, the transcription of genes involved in the stress response (asp23, crtM, and clpB) was not altered by OHM, suggesting that OHM does not induce a general stress response in LAC under the conditions tested (50)(51)(52)(53)(54). Among the metabolism genes examined, OHM had no significant effect on the transcription of the genes involved in electron transport (atpG and sdhA).…”
Section: Resultsmentioning
confidence: 87%
“…Transcriptional response studies have shown a strong induction of the VraSR regulon in response to telavancin treatment, as observed for brilacidin treatment and as expected from a cell wall synthesis inhibitor. Moreover, telavancin highly upregulated the BraDE and VraDE ABC transporters, which are regulated by the NsaSR TCS (61). While brilacidin, daptomycin, and LL16 treatments did cause a large upregulation of the NsaSR regulon, not all members of this regulon were equally affected, and vraD and vraE were significantly upregulated by LL16 treatment only (22-and 35-fold, respectively) (see Table S2 in the supplemental material).…”
Section: Discussionmentioning
confidence: 98%
“…However, only brilacidin and LL16 lead to a significant induction of the lysine biosynthesis pathway (Dap operon), while only brilacidin and daptomycin treatment upregulated cellular proteases and chaperones. The induction of the Dap operon as well as cytoplasmic chaperones/proteases in response to telavancin treatment was also observed (61) and is thought to be a hallmark of membrane The maximal upregulation at any time point under each given condition is reported. Genes with Ͼ3-fold maximal regulation are highlighted in boldface type and underlining.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analyses revealed that after 15 min of exposure to the drug a strong expression of the cell wall stress stimulon (characteristic response to inhibition of cell wall biosynthesis), which was accompanied after 60 min of exposure by an induction of various genes, was also affected by other membrane-depolarizing drugs [34]. These data support a dual mode of action and may explain the bimodal shape of concentration-effect relationships in killcurve experiments [35].…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 67%